Pengaruh Remunerasi terhadap Kinerja Karyawan dan Dimoderasi Oleh Motivasi Kerja Karyawan - Fandy Perdana Putra; Ferryal Abadi (UNIVERSITAS KALBIS, 2022)
This research objective was to know the effect of remuneration to the empployee performance moderated by motivation. This study population is PT. Bona Amiko Kreasi using slovin formula with a total sample of 83 people/ the sampling technique used was purposive sampling. This study uses moderated regression analysis and T-Test. The result of this study indicate that remuneration has a significant relationship to employee’s performance and work motivation can moderate the relationship between remuneration and employee’s performance but the result given work motivation are negative